2010
DOI: 10.1002/jso.21788
|View full text |Cite
|
Sign up to set email alerts
|

Significance of aeg‐1 expression in correlation with vegf, microvessel density and clinicopathological characteristics in triple‐negative breast cancer

Abstract: AEG-1 expression may be related with tumor angiogenesis and progression and is a valuable prognostic factor in patients with triple-negative breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 48 publications
4
51
1
Order By: Relevance
“…The first was its ability to interact and activate the b-catenin pathway (12); and second, the emerging evidence that MTDH/ AEG-1 may coordinate the activity of several signaling pathways all leading to the progression of tumor growth and spread in a number of different tumor types (including glioblastoma; ref. [13][14][15][16][17]. If CPEB1 is regulating the synthesis of MTDH/AEG-1, it would suggest that CPEB1 is coordinating the synthesis of proteins that are functionally related (e.g., b-catenin and MTDH/AEG-1), and that targeting CPEB1-mediated protein synthesis might be useful in many types of cancer not just glioblastoma.…”
Section: Introductionmentioning
confidence: 99%
“…The first was its ability to interact and activate the b-catenin pathway (12); and second, the emerging evidence that MTDH/ AEG-1 may coordinate the activity of several signaling pathways all leading to the progression of tumor growth and spread in a number of different tumor types (including glioblastoma; ref. [13][14][15][16][17]. If CPEB1 is regulating the synthesis of MTDH/AEG-1, it would suggest that CPEB1 is coordinating the synthesis of proteins that are functionally related (e.g., b-catenin and MTDH/AEG-1), and that targeting CPEB1-mediated protein synthesis might be useful in many types of cancer not just glioblastoma.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of MTDH has been frequently observed in a variety of primary human tumors, including breast cancer (7)(8)(9)(10), multiform glioblastoma (11)(12)(13), neuroblastoma (14,15), gastric cancer (16), colorectal carcinoma (17), osteosarcoma (18), gallbladder carcinoma (19), head and neck squamous cell carcinoma (HNSCC) (20) (26), and prostate cancer (6,27,28). Furthermore, published studies on some cancers have revealed that MTDH is a novel and useful prognostic marker for cancer progression, and its overexpression is associated with an unfavorable prognosis (7,8,13,(15)(16)(17)23,24,26,28,29). The role of MTDH in HCC has long been debated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the previous studies have demonstrated that there were many microvessel in IMPC [29] and the VEGF-C high expression was associated with lymph node metastasis of IMPC [30] . The significance of MTDH expression was in correlation with VEGF in triple-negative breast cancer [31] . MTDH is indeed a direct regulator of angiogenesis by up-regulating key components, such as vascular endothelial growth factor (VEGF), which plays an important role in the process of blood vessel formation [32,33] .…”
Section: Discussionmentioning
confidence: 92%